Strategi Pengamatan Lingkungan dalam Pengembangan Kawasan Ciung Wanara Oleh Dinas Parisawata Kabupaten Ciamis - Lidya Widiantie; H. Sirodjul Munir; Dini Yuliani (Pusat Riset dan Inovasi Nasional, 2025)
This research is motivated by the results of initial observations that the Environmental Observation Strategy in the Development of the Ciung Wanara Area by the Ciamis Regency Tourism Office is not optimal. The purpose of this study is to determine the Environmental Observation Strategy in the Development of the Ciung Wanara Area by the Ciamis Regency Tourism Office. The method used in this study is a qualitative research method. There are 5 informants. Data collection techniques are literature studies, field studies (observations and interviews) and documentation. The author uses qualitative data analysis techniques through processing data from interviews and observations to draw conclusions so that they can answer the problems in the study. Based on the results of the study, it is known that: The Environmental Observation Strategy in the Development of the Ciung Wanara Area by the Ciamis Regency Tourism Office is not optimal, this is due to the lack of human resources in the Tourism Office so that it is still rare to provide training to staff, therefore to overcome the obstacles faced in the environmental observation strategy in the development of the Ciung Wanara area, the Tourism Office seeks to provide periodic HR competency improvement training, so that by conducting training, the HR competency owned will increase.